2022
DOI: 10.1088/1674-4926/43/7/072101
|View full text |Cite
|
Sign up to set email alerts
|

Electron mobility anisotropy in (Al,Ga)Sb/InAs two-dimensional electron gases epitaxied on GaAs (001) substrates

Abstract: The electron mobility anisotropy in (Al,Ga)Sb/InAs two-dimensional electron gases with different surface morphology has been investigated. Large electron mobility anisotropy is found for the sample with anisotropic morphology, which is mainly induced by the threading dislocations in the InAs layer. For the samples with isotropic morphology, the electron mobility is also anisotropic and could be attributed to the piezoelectric scattering. At low temperature (below transition temperature), the piezoelectric scat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…2(a). No visible magnetic phase transition can be observed down to 2 K. Between 100 and 300 K, the susceptibility is nearly temperature-independent [32,33]. On the other hand, we found that the paramagnetic susceptibility in the temperature range of 300-400 K can be well fitted with the Curie-Weiss law as shown in fig.…”
Section: Resultsmentioning
confidence: 49%
“…2(a). No visible magnetic phase transition can be observed down to 2 K. Between 100 and 300 K, the susceptibility is nearly temperature-independent [32,33]. On the other hand, we found that the paramagnetic susceptibility in the temperature range of 300-400 K can be well fitted with the Curie-Weiss law as shown in fig.…”
Section: Resultsmentioning
confidence: 49%
“…On the other hand, the M sat in the ab-plane is about 0.2 µ B /Mn. Both the M sat and M eff are comparable to those of (Ga,Mn)As and (Ba,K)(ZnMn) 2 As 2 [29,30].…”
Section: Magnetic Propertiesmentioning
confidence: 60%